Frequency of Postpartum Depression Among Covid-19 Affected Mothers - Choudary, Abeera; Chugtai, Faiqa; Shafqat, Hira; Siraj, Asifa; Abbas, Zainab; Habib, Maria (Pakistan Armed Forces Medical Journal, 2024)
Objective: To evaluate the frequency of Postpartum depression among COVID-19 affected mothers.Study Design: Comparative cross-sectional study.Place and Duration of Study: Obstetrics and Gynaecology Department of PEMH, Rawalpindi Pakistan, from Jun to Aug 2020.Methodology: A validated questionnaire was used to collect patient data regarding demographic profile and after which questions were asked to calculate Edinburgh Postnatal Depression Score from both COVID-19 positive and negative mothers, 6 weeks after delivery. A score of more than 12 was considered statistically significant for postnatal depression.Results: Total number of women included in the study were 50(38% COVID-19 positive). The frequency of postpartum depression was 9(47.4%) among COVID-19 affected mothers and 16(51.6%) in COVID-19 negative mothers. Amongst COVID-19 positive cases, 14(73.7%) were found to be having less than 1 week of COVID-19 positivity, all 19(100%) were practising isolation, 12(63.7%) had less than 7-days of hospitalization,1(5.3%) was admitted in Intensive Care Unit, all were satisfied with staff support, 13(68.5%) had a fear of stigma and 1(5.3%) was found to have fear of unemployment.Conclusion: COVID-19 pandemic has had a strong psychological impact on all postpartum mothers irrespective of their infectivity level. This study has highlighted the alarmingly high frequency of postpartum depression in both COVID-19 positive and negative mothers as indicated by high Edinburgh Postpartum Depression Scores (EPDS)